2006
DOI: 10.4049/jimmunol.177.5.3123
|View full text |Cite
|
Sign up to set email alerts
|

Mutational Analysis of the Mechanism of Negative Regulation by Src Homology 2 Domain-Containing Protein Tyrosine Phosphatase Substrate-1 of Phagocytosis in Macrophages

Abstract: Src homology 2 domain-containing protein tyrosine phosphatase substrate-1 (SHPS-1) is a transmembrane protein predominantly expressed in macrophages. The binding of CD47 on RBCs to SHPS-1 on macrophages is implicated in inhibition of phagocytosis of the former cells by the latter. We have now shown that forced expression in mouse RAW264.7 macrophages of a mutant version (SHPS-1-4F) of mouse SHPS-1, in which four tyrosine phosphorylation sites are replaced by phenylalanine, markedly promoted FcγR-mediated phago… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 36 publications
2
16
0
Order By: Relevance
“…Studies have shown that SIRPα and CD47-mediated cell surface interactions play a critical role in monocyte chemotactic transmigration and macrophage recognition of phagocytic targets. Inhibition of the SIRPα-CD47 interaction delays monocyte transmigration [6] and also perturbs macrophages to elicit intracellular signaling, which normally restrains phagocytosis of the surrounding cells [2,17-22,34]. Consistently, our cell adhesion assays showed that monocytes that had been activated and had transmigrated through the endothelial monolayers or that had differentiated into macrophages displayed significant direct binding to CD47.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…Studies have shown that SIRPα and CD47-mediated cell surface interactions play a critical role in monocyte chemotactic transmigration and macrophage recognition of phagocytic targets. Inhibition of the SIRPα-CD47 interaction delays monocyte transmigration [6] and also perturbs macrophages to elicit intracellular signaling, which normally restrains phagocytosis of the surrounding cells [2,17-22,34]. Consistently, our cell adhesion assays showed that monocytes that had been activated and had transmigrated through the endothelial monolayers or that had differentiated into macrophages displayed significant direct binding to CD47.…”
Section: Discussionsupporting
confidence: 67%
“…It has been suggested that the extracellular binding of SIRPα to CD47 triggers tyrosine phosphorylation in its cytoplasmic ITIMs, resulting in the association of the SH2 domain-containing protein tyrosine phosphatase (SHP-1 or 2), which consequently initiates negative signaling events leading to the inhibition of cell function [11-16]. Studies of macrophage phagocytosis indicate that ligation of macrophage SIRPα by CD47 expressed on the encountered cells prohibits macrophage phagocytosis, whereas failure of SIRPα engagement by CD47, or deficiency of SIRPα ITIM-mediated signaling, promotes macrophage engulfment of the cell [2,8,17-22]. It has also been suggested that increased CD47 expression on cancer cells serves as a crucial mechanism for the evasion of immune clearance [23,24].…”
Section: Introductionmentioning
confidence: 99%
“…Accumulating evidence has shown that ligation of macrophage SIRPα by CD47 expressed on the encountered cells prohibits macrophage phagocytosis, whereas failure of SIRPα engagement by CD47, or deficiency of SIRPα ITIM-mediated signaling, promotes macrophage engulfment of the host cell (1, 3, 4245). Through over-expressing CD47 on the surface, certain types of cancer cells can escape from macrophage-mediated immune clearance (46, 47).…”
Section: Discussionmentioning
confidence: 99%
“…40,41 This signal depends on the docking of SHP-1 phosphatase to phosphorylated ITIMS in the SIRP␣ cytoplasmic domain leading to SHP-1 activation and presumably dephosphorylation of one or more key components of the phagocytic machinery. 42,43 A function of this mechanism is suggested by the report that phagocytosis of xenograft cells is augmented by the species incompatibility of donor CD47 with host SIRP␣. 44 …”
Section: Biological Roles Of Cd47mentioning
confidence: 99%